Impact of the 1999 earthquakes on the outcome of the 2002 parliamentary election in Turkey - Ali T. Akarca; Aysit Tansel (Institute for the Study of Labor (IZA), 2008)
The two major earthquakes which struck northwestern Turkey in 1999, not only caused enormous amounts of death, destruction and suffering, but also exposed rampant government corruption involving construction and zoning code violations. The incompetence shown by the government in providing relief, the corruption allegations in regards to those efforts, and government's failure to prosecute corrupt officials and businessmen, further angered the public. How voters responded to these in the 2002 parliamentary election is investigated, using cross-provincial data, and controlling for other social, political and economic factors. Our results show that voters held accountable all of the political parties which participated in governments during the last decade or so, and not just the incumbents in 2002. The party in charge of the ministry responsible for earthquake relief, and parties that served longest and controlled more of the city administrations in the quake zone were blamed more. The newly formed Justice and Development Party (AKP) was the beneficiary of the votes lost by these parties. The sensitivity shown by the electorate to real and perceived corruption implies that corruption problem will be tractable in Turkey, and can be reduced through increased transparency and democratization.
urn:nbn:de:101:1-2008042506
Keywords: D72; 330; Turkey; earthquake; corruption; election; party preference; Wahlverhalten; Korruption; Baupolitik; Erdbeben; Demokratisierung; Türkei